(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2016)
For scientifically solution of the problem of groundwater development in volcanic regions of the Armenian highland we reinterpreted and summarized the long-term data of geophysical studies, including studies made within Aragats volcanic massif. Our drafted summary map of paleorelief of this territory allows one to draw conclusions about the link between modern and paleo-watersheds and on the distribution of groundwater flow in particular within the Selavmastara River basin.